Diseño y análisis de un enlace descendente en un sistema Cell-Free Massive MIMO para comunicaciones en la banda milimétrica, utilizando modelamiento matemático para mejorar la eficiencia espectral. - Lozano Brito, Rostty Alexander (2026)
Cell-Free Massive MIMO (CF-mMIMO) technology represents a fundamental evolution in advanced wireless networks. Unlike traditional cellular systems based on fixed cells, CF mMIMO eliminates cell boundaries and distributes a large number of cell sites across the coverage area. They operate in a coordinated manner through a central unit, providing greater service uniformity, reduced interference, and more efficient spectrum use. Its distributed architecture enables it to serve all users with similar quality, even in remote or highly congested areas, making it a key technology for scenarios where density, reliability, and performance must remain high. Within this framework, a simulation model of the CF-mMIMO system was developed for the downlink communication, aimed at studying its behavior as a function of three main variables: the number of cell sites, the number of antennas per access point, and the number of users served simultaneously. The simulation was implemented under realistic conditions, incorporating propagation processes, spatial distribution, infrastructure densification, and joint operation of the access points. The results validated the system’s behavior, demonstrating that increasing cell site density and the number of antennas significantly improves performance, while varying the number of users does not produce substantial changes. Overall, the developed model provides a solid foundation for future research and potential real-world deployments of this technology in next-generation networks.